Islamic Banking as a Mechanism for Sustainable Development - chakri, soumaya (Journal of Social Sciences and Humanities, 2022)
An Islamic bank is a banking financial institution to collect and use funds within the scope of Islamic Sharia to achieve development in all its social, economic, environmental and other dimensions, where economic development in Islam goes hand in hand with social, urban, cultural and environmental development, which leads to a balance between various factors and trends. This study aims to identify the role of Islamic banks in achieving sustainable development by presenting the mechanisms used by the Islamic bank such as mediation, zakat and endowment. The article also aims to present the role of the Islamic Development Bank in addressing the issues of sustainable development in Algeria The descriptive approach and the analytical approach were combined in this article, to conclude that the Islamic bank is the most important mechanism for achieving sustainability in economic, social, cultural and even environmental development.